2022
DOI: 10.1111/fcp.12772
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evidence that the anti‐inflammatory effect of synthetic cinnamate‐derived dienes is directly linked to a macrophage repolarization

Abstract: The inflammatory process is a mammalian physiological reaction against infectious agents or injuries. Among the cells involved, the macrophages have a highlighted role during this process. Depending on the inflammatory context, they can polarize into pro-or anti-inflammatory profiles (M1 and M2). In this context, compounds derived from cinnamic acid have demonstrated strong evidence of anti-inflammatory activity; however, the mechanism responsible for this effect remains unclear. In this study, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…NO effect has already been demonstrated in LPSstimulated macrophages [23]. Furthermore, NO results are similar to C. langsdorffii leaf extract [5].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…NO effect has already been demonstrated in LPSstimulated macrophages [23]. Furthermore, NO results are similar to C. langsdorffii leaf extract [5].…”
Section: Discussionsupporting
confidence: 67%
“…In vitro assays have been employed to elucidate the mechanisms underlying the anti-inflammatory effects [22,23]. Kaurenol showed no cytotoxic activity and inhibit NO, IL-6, and IL-10 release induced by LPS.…”
Section: Discussionmentioning
confidence: 99%
“…M1 macrophages produce pro‐inflammatory cytokines such as TNF‐α, IL‐1β, IL‐6, and IL‐12. M2 macrophages secrete anti‐inflammatory cytokines such as IL‐10 and TGF‐β, which promote tissue repair [15]. It is shown that the regulatory effects of ginsenoside RT4 on cytokine production may modulate the innate immune system in mice with colitis, leading to the repair of the injury of colitis.…”
Section: Discussionmentioning
confidence: 99%